Trust-Based Privacy for Internet of Things - Vera Suryani; Selo Sulistyo; Widyawan Widyawan (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Internet of Things or widely known as IOT makes smart objects become active participants in the communication process between objects and their environment. IoT services that utilize Internet connection require solutions to a new problem: security and privacy. Smart objects and machine-to-machine communications in IOT now become interesting research, including that related to security. Privacy, which is a safe condition in which object is free from interference from other objects, is one of the important aspects in IOT. Privacy can be implemented using various ways for examples by applying encryption algorithms, restrictions on access to data or users, as well as implementing rules or specific policy. Trustable object selection is one technique to improve privacy. The process of selecting a trustable object can be done based on past activities or trust history of the object, also by applying a threshold value to determine whether an object is "trusted" or not. Some researchers have studied this approach. In this study, the selection processes of trustable objects are calculated using Modified Ant Colony algorithm. The simulation was performed and resulted in declining graphic trend but stabilized in certain trust value.